Ergonomija kompjutorskih sustava - Vitomir Grbavac (Promet - Traffic&Transportation, 1970)
The paper deals with the elements of ergonomics with reference to computer systems. The issue refers to the accommodation of working environment to the man i.e. the adjustment of conditions and equipment to the needs and requirements of workers. The analysis covers as follows: office furniture, equipment designing, lighting, noise level, temperature values, and humidity and office medical care information.